The Effect of Employee Well-Being and Performance on Sustainable Growth in Global Banking - Andhika Prakasa; Muhammad Tara; Surya Raharja; Puji Harto (Arthatama: Journal of Business Management and Accounting, 2025)
This study aims to analyze the influence of employee well-being and performance as pillars of innovation in supporting sustainable economic growth in the global banking industry. Employing a phenomenological approach, the research explores the lived experiences of employees at Bank Rakyat Indonesia across various strategic units in Jakarta. The findings reveal that employee well-being plays a significant role in enhancing motivation, productivity, and innovative behavior. It also serves as a key factor in adapting to rapid digital transformation and technological disruption. The generational differences between Millennials and Generation Z highlight the need for inclusive and adaptive human resource management policies. Contextualized well-being programs have proven effective in fostering employee engagement, cross-generational collaboration, and organizational resilience. This study recommends a strategic integration of employee well-being, performance, and innovation as the foundation for organizational transformation and a meaningful contribution to sustainable economic development, particularly in facing globalization challenges and realizing the vision of Indonesia Emas 2045.